Absent right superior caval vein (vena cava) with normal atrial arrangement. Issue 5 (May 1987) - Choi, J Y; Anderson, R H; Macartney, F J
Abstract : Eight cases of absent right superior caval vein (vena cava) with normal atrial arrangement from the Great Ormond Street database were reviewed. In each case the right subclavian vein and jugular vein drained into a persistent left superior caval vein through a bridging vein. In six cases the left superior caval vein drained into the right atrium by way of the coronary sinus, and in two cases it drained into the left atrium directly because of the complete unroofing of the coronary sinus. The frontal plane P wave axis was displaced leftwards and upwards in four out of seven cases in which an electrocardiogram was available. No case showed arrhythmia on a standard electrocardiogram preoperatively. Echocardiograms were available in four cases and in each case diagnosis of the anomalous connections of the systemic vein was possible. Only one third of the cases showed a crescentic shadow of the persistent left superior caval vein on chest x ray. A chest x ray and electrocardiogram do not provide the means of reliable diagnosis of this condition, though they may suggest the possibility of its existence. Definitive diagnosis requires cross sectional echocardiography or angiocardiography or both.